Soft Tissue Rheumatological Conditions of Patients Visited in An OPD of a Tertiary Care Hospital - Alam, Zahangir; Barua, Sunam Kumar; Mohajan, Kishore (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Soft tissue rheumatological conditions are common but largely unexplored. So the objective of the present study was to see the different soft tissue rheumatological conditions presenting in OPD of a tertiary care center. Materials and methods: Present observational study conducted on 62 patients visiting the Physical Medicine OPD, Chattogram Maa-O-Shishu Hospital for different soft tissue rheumatological conditions were included in the study. Study period was six months from January 2020 to June 2020. After informed written consent patients were introduced a questionnaire and data was collected. Non-probability sampling method was adopted for the study. Data was analyzed by SPSS-20 Results: Among 62 patients gender distributions of patients revealed male was 24(38.7%) and female was 38(61.3%) and age group showing 15(24.2%) patients were at <30 years, 15(24.2%) patients were at 31-40 years, 13(21.0%) patients were at 41-50 years, 9(14.5%) patients were at 51- 60 years, 9(14.5%) patients were at 61-70 years and 1(1.6%) patient was at >71 years age group. Regarding occupations of the study patients 35(56.5%) patients were service holder, 24(38.7%) were doing business, 1(1.6%) patients was farmer, 1(1.6%) was fisherman and 1(1.6%) patients was housewife. Among all 9(14.5%) patients had DM and same number of patients also has HTN. Diagnosis of the soft tissue rheumatological conditions revealed 13(21%) patients had panter fassitis, 1(1.6%) patient had achillis tendinitis, 4(6.5%) patients had patellar tendinitis, 6(9.7%) patients had trochantaric bursitis, 1(1.6%) had tennis elbow, 3(4.8%) had golfer elbow, 191.6%) had De Quarven’s tenosinovitis, 5(8.1%) patients had trigger finger, 18(29.0%) patients had bicep tendinitis, 4(6.5%) patients had suspinatus tendinitis, 5(8.1%) patients had retrocalcaneal bursitis and 1(1.6%) patient had prepatellar bursitis. Conclusion: Soft tissue rheumatological diseases are common in OPD visits and needs proper attention for better patients care. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 11-13